Study Of Candiduria In Catheterized Icu Patients - NUZHAT FIRDOS; DEEPALI.M.KULKARNI; SANDEEP.L.NILEKAR; SWATI KANT (International Journal of Pharma and Bio Sciences, 2015)
Candiduria is an important nosocomial infection afflicting urinary tract. Candiduria in critically ill patients may be life threatening. The common risk factors for Candiduria are indwelling urinary catheter, antibiotic usage, diabetes mellitus, and prolonged hospitalization. Candida albicans has been reported as the most common causative organism for Candiduria in most of the observational studies, followed by Candida glabrata and Candida tropicalis. Species identification of the Candida causing nosocomial UTI should be an important routine procedure before initiating treatment as some are inherently resistant to fluconazole. The present study was thus envisaged with the aim to study the incidence of Candiduria in the ICU of a rural tertiary care hospital, Ambajogai and to identify Candida isolates upto species level by various phenotypic methods, and study their antifungal susceptibility pattern. Species identification was done by the germ tube test, cornmeal agar morphology, CHROMagar, sugar assimilation and fermentation test.. Antifungal susceptibility was done by disk diffusion method. From 76 urinary samples 35 (46.05%) Candida species were isolated. Candida tropicalis was most commonly isolated species followed by Candida albicans. Resistance to fluconazole, ketoconazole and itraconazole was high in non-albicans group.